Impact of Breast Density Awareness on Knowledge about Breast Cancer Risk Factors and the Self-Perceived Risk of Breast Cancer - Kristina Bojanic; Sonja Vukadin; Filip Sarcevic; Luka Malenica; Kaja Grgic; Robert Smolic; Kristina Kralik; Ines Bilic Curcic; Gordana Ivanac; George Y. Wu; Martina Smolic (Diagnostics, 2020)
Breast density (BD) reduces sensitivity of mammography, and is a strong risk factor for breast cancer (BC). Data about women’s awareness and knowledge of BD are limited. Our aim is to examine whether the BD information disclosure and BD awareness among women without BC are related to their knowledge about BC risk factors. We examined self-reported BC risk perception and its association to BD awareness and level of health literacy. A cross-sectional, single site study included 263 Croatian women without BC who had mammographic examination. Data were collected by interviews using questionnaires and a validated survey. Of the total, 77.1% had never heard of BD, and 22.9% were aware of their BD. Most participants who knew their BD (88.2%, p < 0.001) had higher levels of education. Majority of subjects (66.8%) had non-dense breasts and 33.2% had dense breasts. Subjects aware of their BD knew that post-menopausal hormone replacement therapy (p = 0.04) and higher BD (p = 0.03) are BC risk factors. They could more easily access information about health promotion (p = 0.03). High-BD informed women assessed their lifetime BC risk as significantly higher than all others (p = 0.03). Comprehension of BD awareness and knowledge is crucial for reinforcement of educational strategies and development of amendatory BC screening decisions.